Exploitation of the natural world in Bulgarian science fiction utopias and dystopias of the socialist period (Colloquia Comparativa Litterarum, 2025)
The article examines the exploitation of the natural world and its individual consequences as they are presented in a number of utopian and dystopian novels of Bulgarian science fiction during the socialist period. Attention is first given to the post-1956 scientific and technical utopias that depict the future communist world. In these texts, nature is the enemy and victim of man; there are many scenes of ecocide and of severe industrialisation which changes nature’s landscape in accordance with the to human needs and desires. This exploitation is seen as positive and necessary for the construction of the new human world. However, later, towards the end of the 1970s, Bulgarian science fiction began to develop a more ecological attitude towards nature. The exploitation of the natural world became something characteristic of dystopian texts and the capitalist regimes described in them, albeit this time seen in its destructive aspect.
Keywords: nature; exploitation; utopias; dystopias; socialist period; science fiction